THE USE OF BIG6 STRATEGY IN TEACHING READING COMPREHENSION OF RECOUNT TEXT - Andini, Vita Dwi; Salam, Urai; Sri R, Yanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThis pre experimental research was conducted to know how significant Big6 strategy is in teaching reading comprehension of recount text at the eighth grade students of SMP Negeri 11 Pontianak in academic year 2017/2018. Big6 is strategy used by students to solve puzzle of information problem. The sample of this research was 34 students in class VIII E. The data of study was derived from pre test and post test. The data revealed that the Big6 strategy is an effective strategy that can be used by English teacher as an alternative way to teach reading comprehension in the classroom. The result of the research showed that Big6 strategy affected the students reading comprehension. The studentâ€™s pre test score was 64.44 and the post test was 72.85. Furthermore, the effect size of the significant improvement of the treatment was 2.05. It is categorized as highly effective since it is higher than 0.5. The teacher might put some appropriate variations in applying the strategy considering the situation and condition found in the classroom. Keywords: Big6 Strategy, Teaching Reading Comprehension, Recount Text, Pre Experimental ResearchÂ